Quality Learning Spaces, Resources, Technologies and Constructive Alignment Element in Teaching and Learning (Sains Humanika, 2018)
The purpose of this study is to explore the importance of quality learning spaces and constructive alignment in teaching and learning. The study established by using Teaching and Learning Guiding Principles Instrument (TLGPI) to look out the reliability and validity of the instrument in generating teaching and learning guiding principles (TLGP). Participants consisted of 357 Malaysian teacher educators from ten Malaysian higher teacher education institutions which were selected using cluster sampling technique. TLGPI is an essential instrument to reflect in generating the teaching and learning guiding principles in higher education level in Malaysia. Confirmatory Factor Analysis has validated all 4 items of Quality Learning (QL) construct and also all 4 items of Constructive Alignment (CA) construct of TLGPI whereby all items indicated high reliability and internal consistency. A Confirmatory Factor Analysis also confirmed that a single factor model was used to generate teaching and learning guiding principles.
Keywords: Teaching and learning guiding principles; quality learning spaces; resources and technologies; constructive alignment; higher teacher education institution; confirmatory factor analysis